2004
DOI: 10.1038/modpathol.3800108
|View full text |Cite
|
Sign up to set email alerts
|

A distinct expression pattern and point mutation of c-kit in papillary renal cell carcinomas

Abstract: KIT is expressed not only in tumors derived from hematopoietic stem cells, melanocytes, germ cells, mast cells, and interstitial cells of Cajal, but also in other malignancies such as chromophobe renal cell carcinoma. This pattern of KIT expression prompted us to investigate the expression and mutation of c-kit gene exons 9, 11, 13, 17, and intron 17 in the different subtypes of renal cell carcinomas (n ¼ 66) and non-neoplastic kidneys (n ¼ 12). We found that KIT showed strong immunoreactivity in the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
37
3
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 18 publications
5
37
3
1
Order By: Relevance
“…1 However, Lin et al and we could not identify any mutation within the juxtamembranous and tyrosine kinase domains in all cases. 1,2 The other possibility that cannot be confidently dismissed is that the antibody crossreacts with another unknown cytoplasmic epitope that bears structural similarity with KIT hence it can also be blocked by the blocking peptides.…”
contrasting
confidence: 58%
“…1 However, Lin et al and we could not identify any mutation within the juxtamembranous and tyrosine kinase domains in all cases. 1,2 The other possibility that cannot be confidently dismissed is that the antibody crossreacts with another unknown cytoplasmic epitope that bears structural similarity with KIT hence it can also be blocked by the blocking peptides.…”
contrasting
confidence: 58%
“…1 Our finding that KIT is expressed on the cell membrane of chromophobe renal cell carcinomas (RCCs) corresponds with other recent reports. [2][3][4][5][6] However, there are some controversies on the expression of KIT in normal renal tubular cells and papillary RCCs.…”
supporting
confidence: 79%
“…[2][3][4][5][6] However, there are some controversies on the expression of KIT in normal renal tubular cells and papillary RCCs. [1][2][3][4][5][6] In contrast to our paper, 1 Dr Pan et al proposed that KIT expression in the cytoplasm of normal renal tubular cells and papillary RCCs is due to a technical difference by using EDTA as HIER buffer. In addition, Dr Pan et al suggested that the immunoreactive KIT in the cytoplasm of normal tubular cell and papillary RCC might be an unknown protein with a structural similarity or cross-reactivity with anti-KIT antibody (DAKO, Carpinteria, CA, USA).…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…Since the frequency of MET mutations in sporadic papillary RCCs is low, it is possible that other genes might be involved in this form of renal cancer. In this respect, mutations of the KIT proto-oncogene have been described in 68% of papillary RCC patients (Lin et al, 2004). However, the role of KIT in the pathogenesis of this disease needs to be confirmed by functional studies.…”
Section: The Met-hgf Pathway and Type-1 Papillary Renal Cancermentioning
confidence: 99%